Cyberbullying in the educational process: types and preventive measures - Greba Ildikó; Греба Ілдіко; Bevziuk Maryna; Бевзюк Марина (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Problem Statement. In the contemporary educational environment, cyberbullying is becoming increasingly widespread due to the active use of digital technologies, social networks, and online communication among children and adolescents. Unlike traditional bullying, cyberbullying is characterized by anonymity, rapid information dissemination, and continuous psychological pressure, which complicates its detection and mitigation. Cyberbullying negatively affects the emotional wellbeing, learning motivation, and social adaptation of participants in the educational process. Despite growing attention to the issue, prevention systems remain insufficiently developed, and educators, parents, and students often lack effective strategies for responding. This highlights the need to identify types of cyberbullying, analyze their features, and develop comprehensive preventive measures within the educational process. Analysis of Current Research. Research indicates that cyberbullying and its prevention are actively studied by both international and Ukrainian scholars. International researchers (K. Barrett, R. Kowalski, S. Limber, P. Smith, J. Finkel, J. Yunoven) focus on the factors contributing to cyberbullying, participant roles, and psychological mechanisms. Ukrainian scholars (L. Naidionova, V. Bedan, K. Ivanyuk, A. Tyshchenko, et al.) examine the nature of the phenomenon, classification of its types, and developmental dynamics. Significant attention is given to the destructive impact of cyberbullying on children’s and adolescents’ mental health (Yu. Lehar, M. Ozhevan, O. Petrunko). Other studies (H. Yefremova, Z. Zalibovska, K. Chaban) analyze the role structure of participants and behavioral models in online spaces. Legal aspects of countering cyberbullying are discussed by P. Bilenchuk, M. Dzyuba, V. Lipkan, among others, emphasizing the interdisciplinary nature of the problem.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cyberbullying; measures; education